Analisis Manajemen Fundrising Umar bin Khattab dan Relevansinya dengan Pengelolaan Zakat di Indonesia - Ghosyi Harfiah Ningrum; Mu'min Firmansyah (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2020)
The period of Umar Bin Khattab's leadership was a golden age in the history of Islamic economics. The policies made are able to prove the greatness of the Islamic economic system. The success of Umar also made several zakat management organizations (OPZ) interested in implementing it in their operational activities, especially in gathering or fundraising activities. Using a qualitative literature study method, the writer intends to analyze (1) the functions of fundraising management, then combine them with (2) Umar bin khattab's zakat policy, so that (3) the suitability of Umar's policies in fundraising activities carried out by the management organization zakat (OPZ) to help improve the quality of OPZ performance in collecting zakat. The author obtains primary data sources through several main sources, because he cannot make direct observations and interviews. For secondary data sourced from journals, theses, scientific papers and articles obtained via the internet. The results show that the form of zakat policy made by Umar bin Khattab is not directly suitable for implementation in the current OPZ fundraising strategy. It is necessary to study, analyze and adjust in advance to the conditions and conditions of muzakki and mustahik so that fundraising activities can run effectively and efficiently and in accordance with Islamic sharia rules.